2002
DOI: 10.1016/s0736-0266(01)00169-3
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated expression of scleraxis and Sox9 genes during embryonic development of tendons and cartilage

Abstract: Embryonic development of tendons is in close association with that of cartilage and bone. Although these tissues are derived from mesenchymal progenitor cells which also give rise to muscle and fat, their fates clearly diverse in early embryonic stages. Transcription factors may play pivotal roles in the process of determination and differentiation of tendon cells as well as other cells in the skeletal system. Scleruxis, a basic helix-loop-helix (bHLH) type transcription factor, is expressed in mesenchymal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 20 publications
3
83
0
1
Order By: Relevance
“…In the early phase of embryonic development, the expressions of Scx and Sox9 are overlapped in sclerotome. However, Scx is reduced in the center of Sox9-expresssed sclerotome during the following development [27].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the early phase of embryonic development, the expressions of Scx and Sox9 are overlapped in sclerotome. However, Scx is reduced in the center of Sox9-expresssed sclerotome during the following development [27].…”
Section: Discussionmentioning
confidence: 97%
“…4B). Several authors have indicated that common mesenchymal precursor cells expressing both Sox9 and Scx are involved in the coordinated development of cartilages, tendons, and ligaments [27,28]. In the early phase of embryonic development, the expressions of Scx and Sox9 are overlapped in sclerotome.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Id2 has been involved in the control of cell fate decision between two different cell types in other model systems as the terminal differentiation of different lineages of haematopoietic cells from a common progenitor (Ikawa et al, 2001). Tendons develop in close association with cartilages, and scleraxis, an helix-loop-helix transcription factor promotes the specification of mesenchyme towards the tendon lineage (Asou et al, 2002, Brent et al, 2003. At least in the axial skeleton tendon and cartilaginous fates are alternative and cartilage differentiation is required to actively repress tendon development (Brent et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Scx is a basic helix-loop-helix transcription factor that has been implicated in tendon development and regeneration [2,23,26]. Endogenous expression of Scx defines a zone between sclerotomal and myotomal cells in the developing somite, and persists throughout tendon formation in the mouse embryo [4,5,24,26].…”
Section: Introductionmentioning
confidence: 99%
“…Scx deficiency results in severe tendon defects in mice [21]. Scx also is believed to direct tendinous attachments to bone through its effects on chondrogenic lineage formation [2,4,20]. The simultaneous role for Scx in tendon and cartilage development suggests it has the potential to improve regeneration of the rotator cuff insertion site consisting of the tendon and its cartilaginous transition zone into the bone [6,8,12,17,25].…”
Section: Introductionmentioning
confidence: 99%